Same-Sex Marriage and the Role of Transnational Law: Changes in the European Landscape. Issue 3 (1st June 2016) - Fichera, Massimo
Abstract : This Article has a twofold aim. First, it focuses on a particular case study, which has attracted the interest of several scholars from an interdisciplinary perspective: the legalization of same-sex marriage. The Article aims to show how changes in one specific socio-cultural landscape may spill into other contexts as a result of a ripple effect. The idea is to demonstrate how the emergence of a social fact—the increasing demands made by homosexual couples for their union to be recognized in one way or another—may make the process of institutionalization natural. A legal system may sometimes be bound to recognize social facts, and transnational law may enhance this phenomenon. The second aim of the Article is to claim is that, when analyzing change, legal deterministic theories should be dismissed, as they are based upon easy assumptions that do not correspond to empirical observations. Instead, as shown by constructivist approaches, the combined effect of structure and agency in some specific circumstances contributes to social and legal change. However, constructivists perhaps underestimate the relevance of unpredictable events and the (positive or negative) influence that transnational frameworks may have in forming discourses of power. In particular, the EU and the ECtHR systems may facilitate the diffusion of ideas and norms deriving directly from the liberal paradigm that inspire them. However, the liberal paradigm is contradictory, as it does not necessarily provide an incentive for change.